2022
DOI: 10.3390/app12020849
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Excitation of Various Lamb Waves Modes in Thin Plastic Films

Abstract: Ultrasonic-guided waves are widely used for the non-destructive testing and material characterization of plates and thin films. In the case of thin plastic polyvinyl chloride (PVC), films up to 3.2 MHz with only two Lamb wave modes, antisymmetrical A0 and symmetrical S0, may propagate. At frequencies lower that 240 kHz, the velocity of the A0 mode becomes slower than the ultrasonic velocity in air which makes excitation and reception of such mode complicated. For excitation of both modes, we propose instead a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The best excitation signal of a single sleeve, as verified by Hu Y. [18], is found to be cycle number 4 at a center frequency of 15 kHz, so 15 kHz, and a total of five other frequencies of 5 kHz, 10 kHz, 20 kHz, 25 kHz, and 30 kHz were studied under cycle number 4. The time−domain signals extracted by the secondary receiver are shown in Figure 6.…”
Section: Analysis Of the Best Frequency Verification Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The best excitation signal of a single sleeve, as verified by Hu Y. [18], is found to be cycle number 4 at a center frequency of 15 kHz, so 15 kHz, and a total of five other frequencies of 5 kHz, 10 kHz, 20 kHz, 25 kHz, and 30 kHz were studied under cycle number 4. The time−domain signals extracted by the secondary receiver are shown in Figure 6.…”
Section: Analysis Of the Best Frequency Verification Resultsmentioning
confidence: 88%
“…Research presented in the article of Hu Y. [18] showed that the optimal excitation signal for a single embedded grouting sleeve was determined as the Lamb wave signal of cycle 4 and the frequency of 15 kHz. In this paper, multiple embedded grouting sleeves are studied, and the arrangement forms are distinguished.…”
Section: Verification Of the Optimal Excitation Signal In The Injury ...mentioning
confidence: 99%
See 1 more Smart Citation